Management of Fused Primary Anterior Teeth: A Case Series - Mohamed Salah Shalaby; Osama Ibrahim El Shahawy (Case Reports in Dentistry)
Fusion is a developmental dental anomaly that may affect both dentitions. The condition occurs during the developmental stage when two different tooth buds fuse. Depending on the degree of fusion, teeth may be diagnosed with fusion, gemination, or macrodontia. This defect is typically described as primary double teeth. The main clinical problems associated with primary double teeth include dental caries, crowding, occlusal discrepancies, and poor aesthetics. This report presents the clinical experience of managing 13 primary fused anterior teeth. The aim was to preserve and restore the decayed teeth while maintaining function and aesthetics. Treatment varied from the application of preventive measures to the separation of fused teeth. Clinical and radiographic diagnoses were used to determine the appropriate treatment plan. Decay removal was followed by restoration using either composite or zirconia crowns. Some teeth required pulp treatment before final restoration; therefore, pulpectomy was performed, and the canals were sealed with a calcium hydroxide and iodoform mix. Evaluation criteria included clinical success, gingival health, function, and aesthetic preservation. Follow-up periods ranged from 1 to 4 years. The follow-up of the presented cases demonstrated that the selected preventive, restorative, and surgical approaches successfully retained the affected teeth in a stable and healthy condition.